2015
DOI: 10.1007/s11606-015-3344-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Test Result Notification

Abstract: IMPORTANCE:Patients are increasingly being given access to their test results, but little is known about how preferences vary with the test under consideration or the results of the test (normal or abnormal). OBJECTIVE: This study was conducted to examine preferences for test result communication. DESIGN, SETTING, AND PARTICIPANTS: We surveyed adults to explore their preferences for test result notification for three common diagnostic tests of varying "emotional impact" (dual-energy x-ray absorptiometry [DXA],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Portals may meet those stated needs and caregivers recognized this. Despite this, actual acceptance of portals for result acquisition continues to be low, with 5%–16% of survey respondents ranking a portal first in acceptability . Prior study within the general pediatric population demonstrated that 38% of caregivers enrolled and 26% activated an account between 2007 and 2011 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Portals may meet those stated needs and caregivers recognized this. Despite this, actual acceptance of portals for result acquisition continues to be low, with 5%–16% of survey respondents ranking a portal first in acceptability . Prior study within the general pediatric population demonstrated that 38% of caregivers enrolled and 26% activated an account between 2007 and 2011 .…”
Section: Discussionmentioning
confidence: 99%
“…Many adult patients want immediate access to test results . Portals are one way to move toward this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[11][12][13] In general, both patients and providers are more likely to prefer follow-up visits if results are abnormal and/or carry a high emotional burden. 11,13 The .59…”
Section: Discussionmentioning
confidence: 99%
“…Our tailored letters are a start, but future research needs to explore communication involving different diagnostic tests and using newer communication modalities (e.g., patient portals and text messaging with embedded YouTube links). 20,21 …”
Section: Discussionmentioning
confidence: 99%